Assessing Knowledge, Attitudes and Practice of Hand Washing with Soap among Mothers and Caregivers of Children under Five years in Ntungamo District, Uganda - Topher, Byamukama (Texila International Journal of Public Health, 2020)
Background: The study of hand washing practices in Ntungamo district is part of a larger strategy being implemented in different countries to decrease the prevalence of childhood diarrhea, in the frame work of the global public – private partnership for hand washing with soap. Purpose: This study of hand washing practices using soap in Ntungamo district aimed at reducing childhood diarrhea prevalence in the district. It represents a preliminary study designed to collect the information necessary to design appropriate strategies to reduce diarrhea prevalence in under five years of age. Methods: The study used quantitative and qualitative methods to collect data from a representative sample of several supervision areas of Ntungamo district. Results: The practice of hand washing after latrine use among the respondents was very low (52%) compared to washing hands before and after meals (77%). The study also revealed a low use of soap during hand washing where (52%) who washed their hands after contact with feces, only 14.6% used soap. Whereas whose who washed their hands while handling food were77%, but out of 77% only 28% used soap There was no diarrhea reported among respondents that had A-level education and only 20% of those that had post-secondary education reported having diarrhea episodes among the under-five compared to 64% that reported diarrhea among the under-fives for those that had incomplete primary level of education, 57% among the households of functional adult learning graduates and 49% for those that completed primary level of education.